Broadband Surface‐Enhanced Photoluminescence Based on Gold Nanocubic Self‐Assembly. Issue 23 (9th October 2017) - Ding, Yufeng; You, Yunchang; Sang, Yungang; Wang, Yanrong; Zhao, Man; Liang, Chao; Lu, Chenguang; Liu, Dahe; Zhou, Jing; Tang, Zhiyong; Shi, Jinwei
Abstract: Low‐cost materials with large‐area, broadband, and strong photoluminescence are of great interest in many fields. Plasmonic enhancement structures, based on nanoparticle self‐assembly, are identified as promising candidates for achieving these requirements. This study fabricates Au nanocube assemblies and demonstrates photoluminescence enhancement of quantum dots (QDs) deposited on their surfaces. The enhancement factor of this large‐area ensemble is ≈3.5 with the use of a 532 nm pulse laser to excite red‐emissive QDs. Furthermore, the broadband response of this assembly is studied and enhanced broadband white‐light emission is found. Finally, a new optical information storage method based on this photoluminescence enhancement is demonstrated. The results have significance for applications, such as energy‐saving lighting and displays, solar energy harvesting, optical data storage, and anticounterfeiting measures. Abstract : Plasmonic nanoparticle self‐assembly is identified as one of the most promising techniques to achieve large‐area, broadband, and low‐cost strong photoluminescence. This study demonstrates that Au nanocubic self‐assembly can have an obvious and broadband photoluminescence enhancement effect for quantum dots with different colors. This technique has great potential applications, such as enhanced RGB white‐light emission, optical storage, and anticounterfeiting.